The role of altered fatty acid in pathological scars and their dermal fibroblasts - Jin-Xiu Yang; Shi-Yi Li; Min-Liang Chen; Le-Ren He (Chinese Journal of Traumatology, 2022)
Purpose: The proposed pathological mechanism for scar formation is controversial, and increased attention has been paid to the fatty acids (FAs) in the formation of pathological scars. Notably, FAs are known to be important in inflammation and mechanotransduction, which is closely related to scar formation. Therefore, it is necessary to clarify the roles of FA in scar formation. Methods: Hypertrophic scar and keloid formed for more than a year and without other treatment, as well as normal skin samples were obtained from patients who underwent plastic surgery. Finally, keloids (n = 10), hypertrophic scars (n = 10), and normal skin samples (n = 10) were collected under informed consent. Primary dermal fibroblasts were isolated and cultured. The amount and variety of FAs were detected by lipid chromatography-mass spectrometry. Immunohistochemistry, real-time PCR, and western blotting were used to verify the expression of sterol regulatory element-binding protein-1 (SREBP1) and fatty acid synthase (FASN) in the samples and their fibroblasts. Student's t-test, ANOVA, and orthogonal partial least square discriminant analysis were performed for statistical analysis (∗p < 0.05, ∗∗p < 0.01, ∗∗∗p < 0.001, ∗∗∗∗p < 0.0001). Results: Compared with full-thickness normal skin, there were 27 differential FAs in keloids and 15 differential FAs in hypertrophic scars (∗p < 0.05 and variable influence on projection >1.0). The expression of SREBP1 and FASN was lower in pathological scars both at mRNA and protein levels (all ∗p < 0.05). However, the mRNA levels of SREBP1 (∗∗∗p = 0.0002) and FASN (∗∗∗p = 0.0021) in keloid-derived fibroblasts were higher than that in normal skin fibroblasts (NFBs), while the expression in hypertrophic scar-derived fibroblasts was lower than that in NFBs (both ∗p < 0.05). Whereas there was no significant difference in FASN protein expression between keloid-derived fibroblasts and NFBs (p > 0.05). Conclusion: FAs involved in pathological scars are abnormally changed in scar formation. Thus, fatty acid-derived inflammation and de novo synthesis pathway of FA may play a key role in the formation of pathological scars.